3d metallaelectrocatalysis for resource economical syntheses. (27th May 2020) - Gandeepan, Parthasarathy; Finger, Lars H.; Meyer, Tjark H.; Ackermann, Lutz
Abstract : This review summarizes key developments in 3d metallaelectrocatalysis in the context of resource economy in molecular syntheses. Abstract : Resource economy constitutes one of the key challenges for researchers and practitioners in academia and industries, in terms of rising demand for sustainable and green synthetic methodology. To achieve ideal levels of resource economy in molecular syntheses, novel avenues are required, which include, but are not limited to the use of naturally abundant, renewable feedstocks, solvents, metal catalysts, energy, and redox reagents. In this context, electrosyntheses create the unique possibility to replace stoichiometric amounts of oxidizing or reducing reagents as well as electron transfer events by electric current. Particularly, the merger of Earth-abundant 3d metal catalysis and electrooxidation has recently been recognized as an increasingly viable strategy to forge challenging C–C and C–heteroatom bonds for complex organic molecules in a sustainable fashion under mild reaction conditions. In this review, we highlight the key developments in 3d metallaelectrocatalysis in the context of resource economy in molecular syntheses until February 2020.